Control Characteristic Analysis and Coordinated Strategy Design for Hybrid HVDC With Multi-Infeed MMC Inverters - Zhao, Jingbo; Tao, Yan (Frontiers in Energy Research, 2021)
The hybrid HVDC with cascaded multi-infeed MMC inverters is proposed in recent years and it will be put into reality in near future. But the control characteristic of this hybrid HVDC have not been discussed in details. This paper investigates the control strategy characteristic of the hybrid HVDC using cascaded multi-infeed MMC inverters. By combining the UI curves (the DC voltage and DC current curves) of LCC rectifiers, LCC inverter and MMC inverters, the complete UI curves of the hybrid HVDC are obtained in different control modes. Through the complete UI curve, the characteristic of the control strategy is investigated in different operation situations. It is found that the MMC inverter in DC voltage control could shift to the rectifying mode if the fault occurs or active power orders are intensively changed. To solve such problem, the coordinated control strategy based on the dynamic limiter, diodes and LCC-MMC active orders is proposed in this paper, which can not only prevent the MMC inverter from becoming a rectifier at DC side but also can improve the AC side voltage stability. Nevertheless, the proposed strategy can further endow the MMC with fault ride through abilities. The simulations in PSCAD software verify the correctness and effectiveness of the proposed control strategy.